The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3847/1538-4357/ab5e7b
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Classification and Ionized Gas Outflows in z ∼ 2 WISE-selected Hot Dust-obscured Galaxies

Abstract: We present VLT/XSHOOTER rest-frame UV-optical spectra of 10 Hot Dust-Obscured Galaxies (Hot DOGs) at z ∼ 2 to investigate AGN diagnostics and to assess the presence and effect of ionized gas outflows. Most Hot DOGs in this sample are narrow-line dominated AGN (type 1.8 or higher), and have higher Balmer decrements than typical type 2 quasars. Almost all (8/9) sources show evidence for ionized gas outflows in the form of broad and blueshifted [O III] profiles, and some sources have such profiles in Hα (5/7) or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(65 citation statements)
references
References 161 publications
6
58
1
Order By: Relevance
“…While W1838+3429 has a previously published redshift, the NIRES spectrum does not clearly detect any emission lines, despite the predicted presence of [O III]λ 5007 Å at 2.1 μm based on the redshift from Tsai et al (2015). Similarly, the NIRES spectrum cannot confirm the published redshift of 2.61 for W2016−0041 from Jun et al (2020)…”
Section: Redshift Determinationsmentioning
confidence: 59%
See 3 more Smart Citations
“…While W1838+3429 has a previously published redshift, the NIRES spectrum does not clearly detect any emission lines, despite the predicted presence of [O III]λ 5007 Å at 2.1 μm based on the redshift from Tsai et al (2015). Similarly, the NIRES spectrum cannot confirm the published redshift of 2.61 for W2016−0041 from Jun et al (2020)…”
Section: Redshift Determinationsmentioning
confidence: 59%
“…All targets except W1835+4355 and W2238+2653 have narrow Balmer decrements substantially above the extinctionfree value of 3.1 (Kim et al 2006), indicative of significant extinction at optical wavelengths. Large optical extinctions in Hot DOGs were also reported in Assef et al (2015) and Jun et al (2020). Applying the Balmer decrement/extinction relation from Domínguez et al (2013) with an intrinsic decrement of 3.1 to the measured Hα/Hβ flux ratios gives a mean A V,narrow of 2.4 mag and median of 3 mag, disregarding W1835+4355.…”
Section: Extinction Estimatesmentioning
confidence: 74%
See 2 more Smart Citations
“…Indeed, Díaz-Santos et al (2016) presented a study of the [C II] 157.7 μm emission line in the highest luminosity Hot DOG, and possibly the most luminous galaxy known, WISEA J224607.56-052634.9 (W2246-0526; Tsai et al 2015), and determined based on the emission-line kinematics that the central gas of the host galaxy is likely undergoing an isotropic outflow event. Additional ionized gas outflow signatures have been observed in the optical narrow emission lines of some other Hot DOGs (Wu et al 2018;Jun et al 2020), supporting the presence of strong AGN feedback in the interstellar medium (ISM) of these targets. Assef et al (2015, also see Eisenhardt et al 2012Tsai et al 2015Tsai et al , 2018 showed that the UV through mid-IR SED of the majority of Hot DOGs (specifically "W12-drops" with z>1) can be well modeled as a combination of a star-forming galaxy that dominates the optical/UV emission, and a luminous, obscured AGN that dominates the mid-IR SED and the bolometric luminosity of the system.…”
Section: Introductionmentioning
confidence: 71%